2019
DOI: 10.5114/aoms.2019.86064
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and biochemical assessment of liver damage in albino Wistar rats treated with cytotoxic platinum compounds in combination with 5-fluorouracil

Abstract: Introduction: Chemotherapy-induced hepatotoxicity in cancer patients often results in cessation of therapy and prevents completion of the treatment plan. The entire pathological description and comparison of hepatic damage induced by oxaliplatin or cisplatin in combination with 5-fluorouracil (5-FU) is not adequately reported. This study reports histopathological assessment of hepatotoxicity of a non-tumor bearing organ in rats treated with 5-FU, oxaliplatin and cisplatin (CDDP). Material and methods: Changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…These results are in agreement with Palipoch and Punsawad [ 57 ]. Several studies have identified the hepatotoxic effect of Cis [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with Palipoch and Punsawad [ 57 ]. Several studies have identified the hepatotoxic effect of Cis [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological findings usually collaborate with the results of biochemical and tissue parameters of CP toxicity [52] and in the present study, microvacuolar degeneration and hepatic necrosis are in accordance with the CP hepatotoxic potential (Table 2 and fig. 3C) [53] . On the other hand, in the group treated with CP and LYC, rare microvacuolar degeneration were still present, however to a much lesser extent (Table 2 and fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several clinical trials have shown that OXA represents a viable and reasonable chemotherapeutic option in advanced HCC [19][20][21]; however, high drug resistance and side effect rates greatly limit clinical application of chemotherapy. Therefore, addressing chemotherapy resistance is very urgent and important.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, addressing chemotherapy resistance is very urgent and important. Several studies have explored the efficacy of OXA in combination with other drugs, such as sorafenib, ramucirumab, and ADI-PEG 20 [12][13][14][15][16][17][18][19][20][21][22][23][24]. However, the results of these clinical studies were unsatisfactory, and there are no in-depth studies of the molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%